Reliability of a telephone interview for the classification of headache disorders - Angermaier, Anselm; Koennecke, Andy; Kloetzer, Christine; Strauss, Sebastian; Fleischmann, Robert (Frontiers in Neurology, 2023)
Objective The study aimed to test the reliability of a semi-structured telephone interview for the classification of headache disorders according to the ICHD-3. Background Questionnaire-based screening tools are often optimized for single primary headache diagnoses [e.g., migraine (MIG) and tension headache (TTH)] and therefore insufficiently represent the diagnostic precision of the ICHD-3, which limits epidemiological research of rare headache disorders. Brief semi-structured telephone interviews could be an effective alternative to improve classification. Methods A patient population representative of different primary and secondary headache disorders (n = 60) was recruited from the outpatient clinic (HSA) of a tertiary care headache center. These patients completed an established population-based questionnaire for the classification of MIG, TTH, or trigeminal autonomic cephalalgia (TAC). In addition, they received a semi-structured telephone interview call from three blinded headache specialists individually. The agreement of diagnoses made either using the questionnaires or interviews with the HSA diagnoses was evaluated. Results Of the 59 patients (n = 1 dropout), 24% had a second-order and 5% had a third-order headache disorder. The main diagnoses were as follows: frequent primary headaches with 61% MIG, 10% TAC, 9% TTH, and 5% rare primary and 16% secondary headaches. Second-order diagnosis was chronic migraine throughout, and third-order diagnoses were medication overuse headache and TTH. Agreement between main headaches from the HSA was significantly better for the telephone interview than for the questionnaire (questionnaire: κ = 0.330; interview: κ = 0.822; p < 0.001). Second-order diagnoses were not adequately captured by questionnaires, while there was a trend for good agreement with the telephone interview (κ = 0.433; p = 0.074). Headache frequency and psychiatric comorbidities were independent predictors of HSA and telephone interview agreement. Male sex, headache frequency, severity, and depressive disorders were independently predictive for agreement between the questionnaire and HSA. The telephone interview showed high sensitivity (≥71%) and specificity (≥92%) for all primary headache disorders, whereas the questionnaire was below 50% in either sensitivity or specificity. Conclusion The semi-structured telephone interview appears to be a more reliable tool for accurate diagnosis of headache disorders than self-report questionnaires. This offers the potential to improve epidemiological headache research and care even in underserved areas.